Three New Quinazoline-Containing Indole Alkaloids From the Marine-Derived Fungus Aspergillus sp. HNMF114 - Liu, Sha-Sha; Yang, Li; Kong, Fan-Dong; Zhao, Jia-Hui; Yao, Li; Yuchi, Zhi-Guang; Ma, Qing-Yun; Xie, Qing-Yi; Zhou, Li-Man; Guo, Meng-Fei; Dai, Hao-Fu; Zhao, You-Xing; et al. (Frontiers in Microbiology, 2021)
By feeding tryptophan to the marine-derived fungus Aspergillus sp. HNMF114 from the bivalve mollusk Sanguinolaria chinensis, 3 new quinazoline-containing indole alkaloids, named aspertoryadins H–J (1–3), along with 16 known ones (4–19), were obtained. The structures of the new compounds were elucidated by the analysis of spectroscopic data combined with quantum chemical calculations of nuclear magnetic resonance (NMR) chemical shifts and electron capture detector (ECD) spectra. Structurally, compound 3 represents the first example of this type of compound, bearing an amide group at C-3. Compounds 10 and 16 showed potent α-glucosidase inhibitory activity with IC50 values of 7.18 and 5.29 μM, and compounds 13 and 14 showed a clear activation effect on the ryanodine receptor from Spodoptera frugiperda (sfRyR), which reduced the [Ca2+]ER by 37.1 and 36.2%, respectively.